Mercury's neurotoxicity is characterized by its disruption of selenium biochemistry - Ralston, Nicholas V.C.; Raymond, Laura J. (Biochimica et biophysica acta. General subjects, 2018)
Methylmercury (CH3Hg+) toxicity is characterized by challenging conundrums: 1) “selenium (Se)-protective” effects, 2) undefined biochemical mechanism/s of toxicity, 3) brain-specific oxidative damage, 4) fetal vulnerability, and 5) its latency effect. The “protective effects of Se” against CH3Hg+ toxicity were first recognized >50 years ago, but awareness of Se's vital functions in the brain has transformed understanding of CH3Hg+ biochemical mechanisms. Mercury's affinity for Se is ~1 million times greater than its affinity for sulfur, revealing it as the primary target of CH3Hg+ toxicity. This focused review examined research literature regarding distinctive characteristics of CH3Hg+ toxicity to identify Se-dependent aspects of its biochemical mechanisms and effects. Research indicates that CH3Hg+ irreversibly inhibits the selenoenzymes that normally prevent/reverse oxidative damage in the brain. Unless supplemental Se is provided, consequences increase as CH3Hg+ approaches/exceeds equimolar stoichiometries with Se, thus forming HgSe and inducing a conditioned Se deficiency. As the biochemical target of CH3Hg+ toxicity, Se-physiology provides perspectives on the brain specificity of its oxidative damage, accentuated fetal vulnerability, and latency. This review reconsiders the concept that Se is a “tonic” that protects against CH3Hg+ toxicity and recognizes Se's role as Hg's molecular “target”. As the most potent intracellular nucleophile, the selenoenzyme inhibition paradigm has broad implications in toxicology, including resolution of conundrums of CH3Hg+ toxicity. Mercury-dependent sequestration of selenium and the irreversible inhibition of selenoenzymes, especially those required to prevent and reverse oxidative damage in the brain, are primarily responsible for the characteristic effects of mercury toxicity. This figure shows the electrostatic potential surfaces of mercury in covalent association with the biologically significant chalcogens (oxygen, sulfur, and selenium), their chemical potentials, and binding affinity constants. The electron cloud depicted in blue indicates a lower e− abundance and a more positive charge, while yellow shading to red indicates increasingly negative charge. The balance of the HgSe charges stabilize the molecule, contributing to their remarkably high binding affinities. [Display omitted] •The conundrums of mercury toxicity are consilient from the selenium-perspective.•Mercury toxicity had formerly been assumed to involve binding to cellular thiols.•Mercury's delayed neurotoxicity & fetal vulnerability reflect its effects on selenium.•Thiols help mercury bind selenocysteine-the 21st genetically encoded amino acid.•Mercury inhibits brain selenoenzymes that prevent and reverse oxidative damage.